2020
DOI: 10.21608/resoncol.2020.24758.1091
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of CD56 Expression in Multiple Myeloma

Abstract: Background: Understanding the prognostic markers of multiple myeloma (MM) helps in optimizing therapeutic approaches. CD56 is frequently expressed by malignant plasma cells and its use as a prognostic marker in MM is promising. Aim: To evaluate prognostic value of CD56 expression in patients with MM. Methods: This study included 50 newly diagnosed patients with MM. Bone marrow samples were analyzed for CD56 expression by flow cytometry. All patients received bortezomib-based therapy for at least 3-4 months. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
2
2
1
Order By: Relevance
“…In the present study, hypercalcemia (Ca > 11 mg/dL) was found in 38.3% of patients and a similar ratio was found in the study by Khallaf et al, 2020 [ 15 ]. Median Serum creatinine of 1.7 mg/dL was detected in the present study which was about the same result 1.7 ± 2.1 detected by Udupa et al, 2020 [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, hypercalcemia (Ca > 11 mg/dL) was found in 38.3% of patients and a similar ratio was found in the study by Khallaf et al, 2020 [ 15 ]. Median Serum creatinine of 1.7 mg/dL was detected in the present study which was about the same result 1.7 ± 2.1 detected by Udupa et al, 2020 [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
“…Median Serum creatinine of 1.7 mg/dL was detected in the present study which was about the same result 1.7 ± 2.1 detected by Udupa et al, 2020 [ 2 ]. Renal impairment (serum creatinine > 2 mg/dL) in our study was detected in 38.3% of patients but a lower ratio was detected in 2020 by both Khallaf et al and Warnnissorn et al [ 15 , 16 ]. The higher ratio of renal impairment in this study may be attributed to the higher ratio of renal failure among Africans as stated by an African study in 2018 by Cisse et al [ 17 ].…”
Section: Discussioncontrasting
confidence: 53%
“…This has been the explanation for the leukemic phase of MM being more frequent in patients without CD56 expression in PCs [52]. The absence of CD56 in MM plasma cells was associated with poor prognosis, more aggressive disease [37] and lower PFS [11,19,38] and OS [41,53], however this association was not consensual [9]. Our study showed that the absence of CD56 in clonal PC was associated to significantly higher probability of OS and PFS post ASCT.…”
Section: Discussionmentioning
confidence: 55%
“…По данным некоторых источников, пациенты с ММ с CD56 + имеют более благоприятный прогноз [9], однако в исследовании S. Khallaf и соавт. присутствие данного маркера на ПК было связано с неблагоприятным прогнозом и низкой беспрогрес сивной выживаемостью [10]. При исследовании ИГХ маркеров на опухолевых ПК в нашем исследовании выявлено значимое превышение CD56 + у пациентов с МГНЗ с последующей прогрессией.…”
Section: Discussionunclassified